MODERN DIAGNOSTIC CRITERIA FOR UTERINE FIBROIDS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Uterine fibroids are one of the most common benign neoplasms of the female reproductive system and hold a leading place in the structure of gynecological morbidity. Laboratory parameters, including the evaluation of hormonal status, contribute to a deeper understanding of the pathogenetic mechanisms of the disease. The use of modern diagnostic criteria ensures early detection of uterine fibroids, objective assessment of the growth dynamics of the nodes, and the selection of optimal patient management tactics, which is of great importance for the preservation of women's reproductive health.